Child maltreatment and adult economic outcomes: A systematic review. (January 2023) - Herbert, Laura; Comeau, Jinette; Smith, Carrie; Smith-Carrier, Tracy; Saxby, Christopher; Botelho, Natashia
Highlights: We clarify the relationship between child maltreatment and adult economic outcomes. We use narrative synthesis and harvest plots to systematically review 52 studies. Many studies are unable to demonstrate relationships due to methodological issues. The small but strong prospective evidence base provides evidence for a causal link. Significant gaps remain and the field is fraught with methodological issues. Abstract: Child maltreatment is a major social problem that contributes to a broad range of long-term consequences for both those abused and the wider societies in which they live. This review examines the relationship between child maltreatment and economic outcomes in adulthood via the systematic review of all quantitative research on the topic to date. We highlight the roles of both cross-sectional and longitudinal research and the differential outcomes that emerge based on whether child maltreatment was measured (a) retrospectively or prospectively, and (b) as either a single subtype or combination of types of maltreatment. Our review includes 52 studies, from which we extracted 398 coefficients that represent the association between a wide range of childhood maltreatment types (such as physical, sexual, and emotional abuse) and adult economic outcomes (such as employment, financial strain, and social assistance usage). Although less than half of coefficients (47.7%) can demonstrate a relationship between child maltreatment and economic outcomes in adulthood, there is a robust evidence base resting on prospective data gathered from official records that provides evidence for a causal relationship between child maltreatment and economic outcomes in adulthood. Overall, our findings indicate that the literature is laden with methodological concerns that limit the ability to demonstrate relationships between child maltreatment and economic outcomes in adulthood. Given the important implications of this finding for policy and practice, we make several important suggestions for future research, including the clear and consistent operationalization of both child maltreatment and economic outcome constructs in ways that reflect both individuals' cumulative maltreatment experiences and the multifaceted nature of one's economic situation in adulthood.